2016
DOI: 10.1038/leu.2016.143
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing identifies major DNA methylation changes during progression of Ph+ chronic myeloid leukemia

Abstract: Little is known about the impact of DNA methylation on the evolution/progression of Ph+ chronic myeloid leukemia (CML). We investigated the methylome of CML patients in chronic phase (CP-CML), accelerated phase (AP-CML) and blast crisis (BC-CML) as well as in controls by reduced representation bisulfite sequencing. Although only ~600 differentially methylated CpG sites were identified in samples obtained from CP-CML patients compared with controls, ~6500 differentially methylated CpG sites were found in sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 57 publications
(71 reference statements)
3
52
0
Order By: Relevance
“…This technique has also been used to analyze differences in CpG site methylation in DNA from chronic phase (CP), accelerated phase (AP), and blast crisis (BC) of chronic myeloid leukemia (CML) patients and control individuals. The RRBS analysis showed a higher numbers of methylated CpGs in BC‐CML samples compared with other samples (Heller et al, ). In a recent study using RRBS, Ashktorab et al () reported a list of differentially methylated genes in colorectal neoplasia, tubulovillous adenoma, tubular adenoma, and normal samples.…”
Section: Bisulfite Conversion‐based Methodsmentioning
confidence: 99%
“…This technique has also been used to analyze differences in CpG site methylation in DNA from chronic phase (CP), accelerated phase (AP), and blast crisis (BC) of chronic myeloid leukemia (CML) patients and control individuals. The RRBS analysis showed a higher numbers of methylated CpGs in BC‐CML samples compared with other samples (Heller et al, ). In a recent study using RRBS, Ashktorab et al () reported a list of differentially methylated genes in colorectal neoplasia, tubulovillous adenoma, tubular adenoma, and normal samples.…”
Section: Bisulfite Conversion‐based Methodsmentioning
confidence: 99%
“…It has been reported for years that DNA-level epigenetic regulation plays a causative role in cancer and can thus be targeted for treatment of the disorder (19). In CML, Heller et al observed downregulated expression of many of these genes in BC-CML compared with CP-CML samples, using RNA-sequencing (20). However, a single DNA methylation change may act as a precipitating event in CML progression (21) and may provide a useful basis for revealing new targets of therapy in advanced CML.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers investigate the mutations in IDH1 and IDH2 in acute myeloid leukemia (AML), chondrosarcoma, myelodysplastic syndromes, and cholangiocarcinoma (25)(26). Mutant IDH (mutIDH), and its associated molecular pathways can be an attractive therapeutic targets for AML due to limited treatment option (27). But their prevalence and prognostic impact remain to be explored in large extensively characterized CML and AML.…”
Section: E J M Rmentioning
confidence: 99%